ҚОРАҚАЛПОҚ ХАЛҚ ПЕДАГОГИКАСИДА БОШЛАНҒИЧ СИНФ УКУВЧИЛАРИНИНГ МАНТИҚИЙ ФИКРЛАШ ТУШУНЧАЛАРИНИ ТОПИШМОҚЛАР ОРҚАЛИ ШАКЛЛАНТИРИШ - Ибрагимова, Л.А. (SCIENCE and SOCIETY, 2022)
The article deals with one the most impontant problems of bringing up school children and the influence of works of Karakalpak folklore as fairy tales, riddles, twisters, proverbs and sayings, children’s poem’s and phymes onto children’s psychology. Thein educational role are kevealed on the bage of theoretical and historical aspecta of pedagogics.